A Socio-Rhetorical Analysis of the Cosmic Christ: Colossians 1: 15-20 and its Implications for Environmental Sustainability - Rev. Michael D. Olajide, PhD (Pharos Journal of Theology, 2025)
Due to the increasing rate of environmental degradation, unfavourable climate change, destruction of the ozone layer depletion, chlorofluorocarbons (CFCs) and the like, attention is being given to environmental discourse. Sacred texts such as Colossians serve as heritage for theological and ethical perspective for creation vis a vis environment. The objective of this study is to elicit insights from the pericope (Colossians 1:15-20) for the advancement of environmental sustainability. This objective is accomplished through the use of socio-rhetorical analysis of Colossians 1:15-20 whereby the world within the text and the world behind the text which encompasses the religious, political, socio-cultural and literary genre were examined.